Worse glycemic control, higher rates of diabetic ketoacidosis, and more hospitalizations in children, adolescents, and young adults with type 1 diabetes and anxiety disorders. Issue 3 (2nd February 2021) - Galler, Angela; Tittel, Sascha R.; Baumeister, Harald; Reinauer, Christina; Brosig, Burkhard; Becker, Marianne; Haberland, Holger; Hilgard, Dörte; Jivan, Marcelus; Mirza, Joaquina; Schwab, Julia; Holl, Reinhard W.
Abstract: The aim of the study was to explore the metabolic characteristics and outcome parameters in youth with type 1 diabetes and anxiety disorders. HbA1c levels, rates of severe hypoglycemia, diabetic ketoacidosis (DKA), and hospital admission in children, adolescents, and young adults with type 1 diabetes and an anxiety disorder from 431 diabetes‐care‐centers participating in the nationwide German/Austrian/Swiss/Luxembourgian diabetes survey DPV were analyzed and compared with youth without anxiety disorders. Children, adolescents, and young adults with type 1 diabetes and anxiety disorders ( n = 1325) had significantly higher HbA1c (8.5% vs. 8.2%), higher rates of DKA (4.2 vs. 2.5 per 100 patient‐years), and higher hospital admission rates (63.6 vs. 40.0 per 100 patient‐years) than youth without anxiety disorders (all p < 0.001). Rates of severe hypoglycemia did not differ. Individuals with anxiety disorders other than needle phobia ( n = 771) had higher rates of DKA compared to those without anxiety disorders (4.2 vs. 2.5 per 100 patient‐years, p = 0.003) whereas the rate of DKA in individuals with needle phobia ( n = 555) was not significantly different compared to those without anxiety disorders. Children, adolescents, and young adults with anxiety disorders other than needle phobia had higher hospitalization rates (73.7 vs. 51.4 per 100 patient‐years) and more inpatient days (13.2 vs. 10.1 days) compared to those with needle phobia (all p < 0.001). Children, adolescents, and young adults with type 1 diabetes and anxiety disorders had worse glycemic control, higher rates of DKA, and more hospitalizations compared to those without anxiety disorders. Because of the considerable consequences, clinicians should screen for comorbid anxiety disorders in youth with type 1 diabetes.